Escherichia coli bacterobilia is associated with severe postoperative pancreatic fistula after pancreaticoduodenectomy - Heckler, Max; Mihaljevic, André Leopold; Winter, Dominik; Zhou, Zhao-Ming; Liu, Bing; Tanaka, Masayuki; Heger, Ulrike; Michalski, Christoph; Büchler, Markus W.; Hackert, Thilo (Journal of gastrointestinal surgery, 2020)
The benefit of preoperative biliary stenting in the treatment of pancreatic ductal adenocarcinoma is controversially debated. Data from recent meta-analyses favor primary surgery for the majority of resectable pancreatic cancers. Regardless of this evidence, preoperative biliary stenting via endoscopy (EBS) is commonly performed, often before involvement of a surgeon. The goal of this study was to elucidate the association of bile duct stenting, microbiological dislocation of gut flora to the biliary compartment, and major postoperative complications.